Escherichia Coli - Old and New Insights 2023
DOI: 10.5772/intechopen.100380
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Escherichia coli Probiotics for Improved Health and Disease Management

Abstract: Although natural gut microbiota containsEscherichia coli as a commensal, this bacterium, along with other members of the Enterobacteriaceae family, are usually known for their pathogenic potential. Interestingly, E. coli colonizes first and remains all through life, and in fact, some strains possess beneficial properties such as antibacterial colicin secretion. Among the beneficial strains, E. coli Nissle, isolated in 1917, has been the most extensively explored strain. Adaptability to survive under diverse co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Mutaflor, a branded preparation, is formulated using this active strain and is largely distributed in various countries like Australia, Europe, and Canada (Soundararajan et al, 2019;Pradhan and Weiss, 2020). Besides, Symbioflor 2 and Colinfant are some other commercially available products of E. coli strains (Jacobi and Malfertheiner, 2011;Naresh Kumar and Archana, 2021). EcN is effectively used in the treatment of neuroinflammatory disorders, gastrointestinal disorders like ulcerative colitis, diarrhea, and irritable bowel syndrome (Secher et al, 2017;Manzhalii et al, 2022;Zhao et al, 2022).…”
Section: Escherichia Coli Nissle As Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutaflor, a branded preparation, is formulated using this active strain and is largely distributed in various countries like Australia, Europe, and Canada (Soundararajan et al, 2019;Pradhan and Weiss, 2020). Besides, Symbioflor 2 and Colinfant are some other commercially available products of E. coli strains (Jacobi and Malfertheiner, 2011;Naresh Kumar and Archana, 2021). EcN is effectively used in the treatment of neuroinflammatory disorders, gastrointestinal disorders like ulcerative colitis, diarrhea, and irritable bowel syndrome (Secher et al, 2017;Manzhalii et al, 2022;Zhao et al, 2022).…”
Section: Escherichia Coli Nissle As Probioticsmentioning
confidence: 99%
“…One study demonstrated the in-vitro and in-vivo protective effect of fabricated EcN in the form of matrices consisting of curli nanofibers against dextran sodium sulfate-induced colitis in mice model (Naresh Kumar and Archana, 2021). As mentioned above, EcN is extensively researched for the treatment of intestinal diseases, but its mechanistic approaches to communicating with the host were not established.…”
Section: Escherichia Coli Nissle As Probioticsmentioning
confidence: 99%